Relationships between nutritional intake, appetite regulation, and mental health with body composition among female college students with overweight and obesity - Wang, Qiang; Geok, Soh Kim; Danaee, Mahmoud; Gan, Wan Ying; Zhu, Wang Li; Mai, Yi Qiang; Luo, Sheng Yao (Frontiers in Psychology, 2025)
IntroductionThe prevalence of overweight and obesity among college girls is a significant public health concern. This cross-sectional study investigated the relationships between nutritional intake, appetite regulation, and mental health with body composition among overweight and obese college girls.MethodsThis study involved 72 college girls. Standardized instruments measured the corresponding variables. The data analysis utilized Pearson and Spearman correlations.ResultsResults show that energy and carbohydrate intake were positively correlated with body fat percentage and waist circumference (both p ≤ 0.007). Fat intake was positively correlated with all body composition variables (all p < 0.001). Anxiety was negatively correlated with all body composition variables (all p ≤ 0.027). Hunger at 0 min was positively correlated with body fat percentage and waist circumference (both p ≤ 0.002). Hunger at 60 min was positively correlated with BMI and waist circumference (both p ≤ 0.012). Desire to eat at 0 and 60 min were positively correlated with all body composition variables (all p ≤ 0.003). Desire to eat at 30 min was positively correlated with BMI (p = 0.005). Desire to eat at 90 min was negatively correlated with body fat percentage (p = 0.047). Fullness at 0 min was positively correlated with waist circumference (p = 0.040). Fullness at 30 min was positively correlated with body fat percentage and waist circumference (both p ≤ 0.018). Fullness at 120 min was negatively correlated with all body composition variables (all p ≤ 0.023). Prospective food consumption at 0 min was positively correlated with all body composition variables (all p < 0.001). Prospective food consumption at 30, 60, and 120 min was positively correlated with BMI (all p ≤ 0.008).DiscussionOverall, overweight and obese college girls should manage energy intake, fat intake, carbohydrate intake, anxiety, and appetite regulation to reduce fat levels. Further research suggests exploring counterintuitive correlations between body composition with anxiety, desire to eat at 90 min, and fullness at 0 and 30 min, along with limitations related to causal relationships, measurement accuracy, the relationship with physical activity, and population diversity.